1985
DOI: 10.1002/chin.198505277
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS AND PROPERTIES OF ACETYLENIC ORGANOCHLOROSILANES

Abstract: Die Dichlorsilane (I) reagieren mit den Butyl‐ oder Phenyl‐acetyliden des Natriums (II) zu den Chlorethinyl‐silanen (IIIa)‐(IIId).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…NMR spectra were measured with a DPX 400 Avance (Bruker) with tetramethylsilane Me 4 Si (TMS) as internal standard for 1 H, 13 C, and 29 Si. The external standards for 14 N, 59 Co, and 95 Mo were nitromethane (CH 3 NO 2 ), 0.1  K 3 [Co(CN) 6 ] solution in D 2 O, and 1  alkaline Na 2 MoO 4 solution in H 2 O, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…NMR spectra were measured with a DPX 400 Avance (Bruker) with tetramethylsilane Me 4 Si (TMS) as internal standard for 1 H, 13 C, and 29 Si. The external standards for 14 N, 59 Co, and 95 Mo were nitromethane (CH 3 NO 2 ), 0.1  K 3 [Co(CN) 6 ] solution in D 2 O, and 1  alkaline Na 2 MoO 4 solution in H 2 O, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, broadened 1 H and 13 C NMR signals for the cyclopentadienyl group and small additional peaks indicated that isomerization processes occurred in solution. The 59 Co NMR, IR, and UV/Vis data were typical for alkyne Co 2 (CO) 6 complexes. [40][41][42][43][44] Scheme 5.…”
Section: Alkyne Complexesmentioning
confidence: 99%
See 3 more Smart Citations